PENGARUH LOCUS OF CONTROL, KOMITMEN ORGANISASI, KINERJA AUDITOR, DAN TURNOVER INTENTION PADA PERILAKU MENYIMPANG DALAM AUDIT - Agung Basudewa, Dewa Gede; Lely Aryani Merkusiwati, Ni Ketut (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
Deviant behavior in the audit is behavior that deviates from the standard auditor in carrying out audits audits which can degrade the quality of the audit. This study aims to determine the effect Locus Of Control, Organizational Commitment, Performance Auditor, and Turnover Intention on Deviant Behavior In Audit in Public Accounting Firm (KAP) in Bali. Method of determining the sample in this research is purposive sampling technique based on the consideration (judgment sampling). Respondents in this study amounted to 53 auditors around the KAP in Bali. This study tested using linear regression analysis using SPSS for windows 15:00. Based on the results of the analysis can be concluded that Locus Of Control and Turnover Intention positive and significant impact on Deviant Behavior In the audit, while variable Orginasasi Commitment and Performance Auditor negative Influential and signifinkan on Deviant Behavior In Audit.
Keywords: Locus Of Control; Organizational Commitment; Performance Auditor; Turnover Intention; Deviant Behavior In Audit